UNIT 6F.2 Genetic Manipulation of Stenotrophomonas maltophilia. Issue 1 (1st May 2015) - Welker, Elliott; Domfeh, Yayra; Tyagi, Deepti; Sinha, Sanjivni; Fisher, Nathan
Abstract : Stenotrophomonas maltophilia is a Gram‐negative, aerobic, motile, environmental bacterium that is emerging as an important nosocomial pathogen with high rates of attributable mortality in severely ill patients. S. maltophilia is of particular concern to patients suffering from cystic fibrosis (CF) as it has been shown to colonize airway epithelial and establish a chronic infection. Here we describe several molecular techniques for the genetic manipulation of this bacterium, including DNA extraction, RNA extraction, conjugation of plasmids from Escherichia coli and allelic exchange. © 2015 by John Wiley & Sons, Inc.